Determinants for the transition from work into retirement in Europe - Monika Riedel; Helmut Hofer; Birgit Wögerbauer (IZA Journal of European Labor Studies, 2015)
We use the labor force ad hoc module "transition from work into retirement" to analyze the link between individual as well as pension system characteristics and planned retirement age within the European Union. We find that timing of retirement is correlated between partners who are, already at the stage of retirement planning. In richer countries of the EU15, standard retirement age seems to have a larger effect on planned retirement age than in poorer EU15 states or in new EU member states. The effect of pension wealth is largest in the new EU member states and smallest in rich EU15 countries. Furthermore, industry and occupation effects differ by country type.
Keywords: C21; J22; J26; 330; Planned retirement; Joint retirement decision; Pension system characteristics; Country differences; Europe